"I know you think I think – therefore I am". Mentalisation based therapeutic community: a description. Issue 1 (10th April 2017) - Ruscombe-King, Gillie; Mackenzie, Laura; Pearce, Steve; Saunders, Kate
Abstract : Purpose: The mentalisation based therapeutic community (MBTC) is a group experience which promotes the acquisition of the capacity to mentalise. Members of the community gain greater emotional stability and psychological robustness. The paper aims to discuss these issues. Design/methodology/approach: MBTC works with three theoretical principles: the intrapsychic, interpersonal and social. It is a slow open group where each member completes a ten-week course. The approach is deliberately non-interpretive with an emphasis on personal responsibility and accountability in order to promote clarity of mind. Findings: The authors' experience is that the model engages group members with few drop outs. Originality/value: The combination of mentalising and the use of therapeutic community principles within in MBTC has enhanced outcomes for group members.